2014
DOI: 10.7314/apjcp.2014.15.1.455
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Clustering in Kanagawa, Japan: A Geographic Analysis

Abstract: Background: The purpose of the present study was to determine geographic clustering of breast cancer incidence in Kanagawa Prefecture, using cancer registry data. The study also aimed at examining the association Materials and Methods: Incidence data were collected (e.g., city, special ward, town, and village) in Kanagawa by an indirect method using Kanagawa female population data. Spatial scan statistics were used to detect any area of elevated risk as a cluster for breast cancer deaths and/ regions. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…It is worth pointing out that other studies have used FSSS to identify spatial clusters of other health outcomes such as measles (Tang et al, 2017), cancer (Katayama et al, 2014;Amin, Nelson & McDougall, 2018), suicide mortality (Yamaoka et al, 2020), and cardiovascular diseases (Roberson et al, 2019;Odoi et al, 2019). Recent research in Florida has demonstrated that FSSS is a useful technique for the identification of geographic disparities in stroke prevalence (Roberson et al, 2019) and hospitalizations due to myocardial infarction (Odoi et al, 2019).…”
Section: Spatial Patterns and Clusters Of Pre-diabetes Prevalencementioning
confidence: 99%
“…It is worth pointing out that other studies have used FSSS to identify spatial clusters of other health outcomes such as measles (Tang et al, 2017), cancer (Katayama et al, 2014;Amin, Nelson & McDougall, 2018), suicide mortality (Yamaoka et al, 2020), and cardiovascular diseases (Roberson et al, 2019;Odoi et al, 2019). Recent research in Florida has demonstrated that FSSS is a useful technique for the identification of geographic disparities in stroke prevalence (Roberson et al, 2019) and hospitalizations due to myocardial infarction (Odoi et al, 2019).…”
Section: Spatial Patterns and Clusters Of Pre-diabetes Prevalencementioning
confidence: 99%
“…Other relatively new developments regarding cancer registries include focusing on clustering, for example of breast cancer in Japan[42] and colorectal cancer in Malaysia[43]. Demonstration of quality of care measurement using the Japanese liver cancer registry has been reported[44] and improving trends in ‘cure’ fraction from colorectal cancer by age and tumour stage between 1975 and 2000 was established using population-based data for Osaka[45].…”
Section: Cancer Burden and Cancer Registriesmentioning
confidence: 99%
“…Thus, some studies have already attempted to monitor cancer‐related data on the basis of smaller units, such as cities, counties, towns, and even villages . Monitoring cancer‐related data on the basis of smaller units might not only obtain detailed information about the cancer incidences or mortalities, but also identify the potential clusters more accurately . The spatial statistical analysis developed by Kulldorff and Nagarwalla has been proved to be an effective method for discerning geographical patterns and detecting spatial clusters based on smaller units …”
Section: Introductionmentioning
confidence: 99%